Identification of an Arabidopsis mitochondrial succinate-fumarate translocator - Catoni, Elisabetta; Schwab, Rebecca; Hilpert, Melanie; Desimone, Marcelo; Schwacke, Rainer; Flügge, Ulf-Ingo; Schumacher, Karin; Frommer, Wolf B. (FEBS letters, 2003)
Complementation of a yeast acr1 mutant carrying a deletion of the succinate/fumarate carrier gene enabled functional identification of a mitochondrial succinate translocator from Arabidopsis thaliana (AtmSFC1). Thus complementation of yeast mutants is applicable also for identification and characterization of organellar transporters. Reverse transcription polymerase chain reaction and promoter-GUS fusion showed expression of AtmSFC1 in 2 day old dark grown seedlings, which declined in cotyledons during further development, consistent with a role in export of fumarate for gluconeogenesis during lipid mobilization at early germination of Arabidopsis seeds. In mature plants, expression was found in developing and germinating pollen, suggesting a role in ethanolic fermentation.